Don’t Depend on the Denominator: Closing Deficits is Key to Public Debt Sustainability - Ellis, Colin (Archives of Business Research, 2024)
In recent years, governments have increasingly stepped into shore up their economies when confronted with major shocks, borrowing vast sums to prop up activity. But when considering overall fiscal sustainability, policymakers in advanced economies often focus on the difference between economic growth and the interest rate paid of their debt. Too often, this has led to a focus on growth as the primary means of reducing public indebtedness, with countries still running fiscal deficits. This paper challenges this narrative in Europe by examining how debt burdens in Italy and France would have evolved, with the weaker growth that would have been seen if fiscal deficits had matched Irish outcomes over the past ten years. It demonstrates clearly that actively closing deficits – even with the economic pain that causes – is a better means of ensuring fiscal sustainability than simply limiting deficits to 3%.